Towards Building a Functional Whole-of-Government M&E System for Zambia: The Supply Side - Kanyamuna, Vincent (Advances in Social Sciences Research Journal, 2021)
Monitoring and Evaluation Systems have been identified the world over as powerful tools for good governance, they provide relevant information about development projects, programmes and policies. For that reason, governments, bilateral and multilateral development agencies, including civil society organisations have adopted M&E systems to better their performance through accountability, feedback loops and continuous learning mechanisms. This study investigated the functional status of Zambia’s public sector M&E system. Using a designated diagnostic checklist and analytical framework, the country’s whole-of-government M&E system was found to be weak in several aspects. Specifically, the study argues that for any M&E system to function satisfactorily, it is required that both its ‘supply-side’ and ‘demand-side’ are well developed and sustained. The diagnostic findings have revealed that Zambia’s whole-of-government M&E system had both its supply-side and demand-side weak. However, the study has not focused on both sides, instead, the supply-side has been fully explored and clear suggestions for improvement are made herein. Consequently, the study has proposed a new model which when implemented would holistically strengthen the Government –wide system for M&E. It remains to the powers that be to adopt and implement the recommended model. Government will need to strengthen and sustain its M&E political championship, restructure all government functions towards a results-based management approach—statistics, information technology, skills, policies, laws, etc to support an M&E regime. Likewise, the issues covered in the proposed model could also be of use to other organisations seeking to strengthen their M&E systems. Particularly, the methodology used to undertake the needs analysis could be of utmost applicability by others before embarking on a fuller process of building and strengthening their systems for M&E. Another study was underway to support the demand-side of Zambia’s M&E system.